2015
DOI: 10.3762/bjoc.11.108
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the size of a redox-active tetrathiafulvalene-based self-assembled ring

Abstract: SummaryThe synthesis of a new Pd coordination-driven self-assembled ring M6L3 constructed from a concave tetrapyridyl π-extended tetrathiafulvalene ligand (exTTF) is described. The same ligand is also able to self-assemble in a M4L2 mode as previously described. Herein, we demonstrate that the bulkiness of the ancillary groups in the Pd complex allows for modulating the size and the shape of the resulting discrete self-assembly, which therefore incorporate two (M4L2) or three (M6L3) electroactive exTTF sidewal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…An established pathway to spherical structures involves the careful design and synthesis (often multi-stage) of an organic ligand with precisely spaced functional groups. Nanocapsules can be produced via reversible covalent bonds such as disulfide1314, boronic esters1516 and imines171819202122 or supramolecular interactions such as coordinative bonds23242526 and hydrogen bonding2728293031, the last being exemplified in the present work.…”
mentioning
confidence: 97%
“…An established pathway to spherical structures involves the careful design and synthesis (often multi-stage) of an organic ligand with precisely spaced functional groups. Nanocapsules can be produced via reversible covalent bonds such as disulfide1314, boronic esters1516 and imines171819202122 or supramolecular interactions such as coordinative bonds23242526 and hydrogen bonding2728293031, the last being exemplified in the present work.…”
mentioning
confidence: 97%
“…The resulting 1 H-NMR spectrum exhibits a single set of well resolved signals as anticipated from a symmetrical discrete self-assembly ( Figure 2). H4 and H5 signals are upfield shifted compared to ligand L4Pyr due to through-space interactions between the coligand phenyl units (dppf) and the pyridyl groups, confirming coordination to the metal center [22,24]. A 1 H-NMR DOSY experiment revealed a single set of signals that confirms the formation of a unique discrete species.…”
Section: Resultsmentioning
confidence: 91%
“…In the course of our research related to the preparation of electron-rich self-assemblies [17,[19][20][21][22][23][24][25][26], we have recently demonstrated that the 9-(1,3-dithiol-2-ylidene)fluorene moiety, which is known to be readily and reversibly oxidized into a cation-radical [27,28], can be used as a building-block for the construction of electro-active self-assembled cages [29]. In line with this work, we describe herein the synthesis of an original electron-rich M 2 L 2 metalla-macrocycle constructed from the cis-blocked Pd(dppf)OTf 2 Pd(dppf)OTf2 (dppf = 1,1′-Bis(diphenylphosphino)ferrocene) acceptor and a 9-(1,3-dithiol-2-ylidene)fluorene ligand (L4Pyr) that incorporates two pyridin-4-yl units in the corresponding 3,6-positions.…”
Section: Introductionmentioning
confidence: 99%
“…Prismatic structures are not the only possible outcome for reactions of tetratopic N‐donor ligands with cis ‐blocked Pd II or Pt II complexes. If the ligand can adopt a concave geometry, it is possible to form M 4 L 2 ‐type structures . These complexes do not qualify as prisms, even though they can show a barrel‐like geometry.…”
Section: Introductionmentioning
confidence: 99%